Key Factors Shaping Purchase Intentions for New Energy Vehicles in Urumqi, China - Yuanyuan, He; Krishnan, Vijayaletchumy; Pentang, Jupeth T. (Journal of Ecohumanism, 2024)
Due to the increasing awareness of the United Nations’ Sustainable Development Goals (SDGs) in China, there has been a notable shift in consumer behavior, with more individuals choosing to purchase new energy vehicles (NEVs) as their personal transportation. In response, the Chinese government has implemented policies to encourage NEV adoption. This study uses Urumqi as a sample area to examine the impact of personal preferences, social influences, and government policies on consumer behavior, specifically the intention to purchase NEVs in China. The research is based on the Theory of Planned Behavior (TPB). The findings reveal that consumer behavior in adopting NEVs is significantly influenced by social factors, including peer attitudes and behaviors, along with government support policies.